Calvin and the Bible - McKim, Donald K. (Cambridge University Press, 2006)
During the past several decades a growing number of scholars have come to appreciate the importance of studying John Calvin's interpretive work as a commentator on Scripture in addition to his better-known writings on theology. In this volume ten essays by scholars specializing in Calvin's exegetical methods examine the approaches and themes Calvin emphasized when he interpreted major portions of Scripture. These essays focus on Calvin's work in his biblical commentaries with appropriate cross-referencing to his other writings, including his sermons. A concluding essay synthesizes the main features of what has gone before to present an overall view of John Calvin as an interpreter and commentator on Holy Scripture. An appreciation of Calvin's exegetical labors and his work as a biblical commentator are now recognized as key elements in Calvin scholarship.